2019 ACR/EULAR classification criteria and therapy in predicting organ damage accrual in patients with childhood-onset systemic lupus erythematosus: A retrospective study over the last 29 years. (June 2022) - Kifer, Nastasia; Sestan, Mario; Frkovic, Marijan; Kifer, Domagoj; Kozmar, Ana; Padjen, Ivan; Potocki, Kristina; Anic, Branimir; Batinic, Drago; Malcic, Ivan; Jelusic, Marija
Objective: We explored damage occurrence in patients with childhood-onset SLE (cSLE) and aimed to predict the risk of organ damage occurrence in time. Methods: The retrospective study included patients treated for cSLE at the Centre of Reference for Pediatric and Adolescent Rheumatology of the Republic Croatia over a 29-year period. Results: The disease development of 97 patients (77 females) with cSLE was examined. The median (Q1, Q3 ) follow-up time was 6.5 (2.3, 12.0) years. SDI was determined at 5 time points (6, 12, 24, 36 months, and last follow-up). Thirty-eight patients (48%) had organ damage at the last follow-up. Prepubertal group of patients showed higher SLEDAI scores at the disease onset, while post-pubertal group had significantly lower proportion of patients with relapses. We estimated the time from the first symptom to the moment of damage and our findings suggest that it is unlikely that organ damage will occur in 50% of patients in the first 6 years since the diagnosis. The number of 2019 ACR/EULAR classification criteria at the time of diagnosis associated with SDI determined after 1 year of the follow-up period. The patients who received higher doses of glucocorticoids accumulated damage faster and mycophenolate mofetil was found to be a more frequent therapy in patients with SDI ≥3. Conclusion: Knowing that damage will most likely happen after the first 6 years after diagnosis in 50% of patients enables physicians to better predict damage occurrence. High number of 2019 ACR/EULAR criteria and treatment with glucocorticoids in childhood-onset SLE are associated with damage accrual and these findings could enable us to detect patients which should be closely monitored for higher risk of damage development.